Faktor yang Mempengaruhi Perilaku Pembelian Sayuran Organik Studi Kasus pada Konsumen Sayuran Organik di Jabodetabek - Prasiyuda, Eka; Andriani, Meta (STIE Indonesia Banking School, 2024)
This study aims to examine the Factors Influencing Organic Vegetable Purchasing Behavior Case Study on Organic Vegetable Consumers in Greater Jakarta. The sample in this study consisted of 50 respondents. The analysis method used is Partial Least Square. The results of the analysis showed that price on attitude had a negative and insignificant influence on organic vegetable buying behavior. Subjective norms and attitudes on purchase intention have a positive and significant influence on organic vegetable purchasing behavior. Purchase Intention on purchasing behavior has a positive and significant influence on organic vegetable purchasing behavior. Environmental knowledge, environmental concerns, advertising, long-term orientation and price quality on attitudes have no influence on organic vegetable purchasing behavior.